(untitled) (ENTHYMEMA, 2013)
Starting from some notes on the ‘transfiguration’ of personal memories on the written page, this essay uncovers the problems that actress Eleonora Duse had with the publication of D’Annunzio novel The Flame. Although the actress didn’t forbid the publication, she suffered because of the portrayal of the Foscarina character, modelled on herself: it was through a private conversation with a young fan, Noemi Carelli De Agostini, that Duse could revise her opinion on the book and forgive D’Annunzio. Also, the conversation made Duse conscious of the importance of her art and of the way it could be bequeathed to posterity.